The Safety and Feasibility of Laparoscopic Gastrectomy after Neoadjuvant Chemotherapy for Locally Advanced Gastric Cancer. (31st May 2022) - Ge, Rui; Liu, Kai; Zhang, Weihan; Yang, Kun; Chen, Xiaolong; Zhao, Linyong; Zhou, Zongguang; Hu, Jiankun
Abstract : Background . Neoadjuvant chemotherapy is incrementally applied to remedy locally advanced gastric cancer. However, NACT also enhances the difficulty of laparoscopic lymph node dissection. The objective of our study was to evaluate the safety and feasibility of laparoscopic gastrectomy for locally advanced gastric cancer after neoadjuvant chemotherapy. Methods . From July 2017 to December 2019, 153 patients who received neoadjuvant chemotherapy and underwent the subsequent surgical procedure were retrospectively enrolled and analyzed in the Gastrointestinal Surgery Department of West China Hospital. According to surgical methods, all the patients were sectionalized into two groups: laparoscopic assistant gastrectomy (LAG, 77 patients) and traditional open gastrectomy (OG, 76 patients). The demographic parameters, preoperative, surgical, pathological, and neoadjuvant chemotherapy features were compared between the two groups. Results . A total of 153 patients accepted neoadjuvant chemotherapy and surgical resection in our study. There was no statistically significant difference in demographic parameters and preoperative and neoadjuvant chemotherapy characteristics between the two groups. The LAG group illustrated less intraoperative blood loss (91.1 ± 53.1 ml vs. 125.7 ± 116.9 ml, p = 0.010 ) and shorter postoperative hospital stays (7.9 ± 2.1 days vs. 125.7 ± 116.9 days, p = 0.009 ), when compared to the OG group. Moreover, there was no disparity with respect to operative duration, number of harvested lymph nodes, and postoperative complication rates between the two groups. When considering the Clavien–Dindo classification, no statistically significant difference was indicated in all stratifications with regard to postoperative complications. Conclusion . Laparoscopic gastrectomy for locally advanced gastric cancer after neoadjuvant chemotherapy is safe and feasible without increasing postoperative adverse events.